Effect on Corporate Governance and Profitability Information Disclosure - Prayudi, Arditya; Kholisoh, Dr. Luluk (Accounting, 2010)
This study aims to see the impact of the implementation of corporate governance on the disclosure of information. Implementation of corporate governance and disclosure are the two subjects that can protect investors from the asymmetry of information. In this study, the sampling method used was purposive sampling of selected samples from populations with certain criteria, namely the companies that entered in the 10 top ranking conducted by IICG from 2003-2008. Variables tested in this study consisted of disclosure of information to be seen impact on the implementation of Corporate Governance. Corporate Governance and profitability variables were also tested its effect on the level of disclosure. The analysis used in this research is descriptive statistics, normality test, the classical assumptions and multiple regression analysis. From the regression analysis conducted, it can be concluded that the implementation of the Corporate Governance significantly influence the level of disclosure of a company. Companies with high corporate governance index will reveal better information in the financial statements. Vice versa, companies that provide high disclosures in the financial statements will show that the implementation of Corporate Governance in the company, the better Keywords: Corporate Governance, Disclosure of information.